Efektivitas Gel Ekstrak Biji Putat Air [Barringtonia racemose (L) Spreng] terhadap Penyembuhan Luka Diabetik di Perawatan Luka Asri Medan - Nur Asnah Sitohang; Effendy De Lux Putra (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2022)
Diabetes mellitus (DM) is a serious chronic disease that occurs when the pancreas does not produce enough insulin (a hormone that regulates blood sugar or glucose), or when the body cannot effectively use the insulin it produces. The basic health research report (RISKESDAS), shows that the prevalence of diabetes mellitus in Indonesia is 6.9%. North Sumatra data on the prevalence of diabetes mellitus is 1.8% or around 160 thousand people. Problems that arise in patients with DM include the emergence of DM ulcers. These diabetic ulcers or wounds usually often occur on the hands or feet of the patient. The prevalence of diabetic wounds in Indonesia is around 15%, the amputation rate is 30%, the mortality rate is 32% and diabetic wounds are the most common cause of hospitalisation at 80%. A natural material that can be used as an alternative biological therapy for wound management is putat air [Barringtonia racemosa (L). Spreng]. This plant contains many saponins that are useful as anti-inflammatory, antinociceptive and help the proliferation process by increasing collagen production. The effectiveness and convenience of using putat air (B. racemosa) seed extract on diabetic wounds is improved by formulating it into a gel dosage form with carbopol 940 as the base material. This study aims to identify the effectiveness of putat air (B.racemosa) seed gel on diabetic wound healing. The research design was quasy experiment pre post design. The number of samples was 32 people. The sampling technique was total sampling. The research was conducted at Asri Wound Clinic Medan. The instrument used for diabetic wound monitoring was Bates Jonson Assessment Tool (BWAT). Data analysis using paired t test. The results of the wound assessment of respondents for 4 times with an interval of 4 days. The 4th observation showed a decrease in score. Based on the BWAT wound healing continuum, the respondents' wound conditions were still in the wound degeneration phase. The majority of the wound area < 80cm; stage 3 depth; clear wound edges, not fused with the wound bed, GOA 2-4 cm > 50%; the edge of necrosis tissue is sticky, soft and there is black false scarring (black eschar); the amount of necrosis tissue > 50% of the wound bed; the skin colour around the wound is dark red; oedematous tissue < 4mm around the wound; granulation tissue 25 and epitalisation < 25%. The statistical test results of the difference in mean 3.782 and P value = 0.001 (<0.05), it can be concluded that there is a significant difference in the wound healing scores of respondents before and after the intervention. This study proves that the gel of putat air (B. racemosa) seed extract can be used as an alternative to diabetic wound healing, especially in the inflammatory phase as auotolysis.